2007
DOI: 10.1007/s00726-007-0524-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine contents in current foods: a basis for polyamine reduced diet and a study of its long term observance and tolerance in prostate carcinoma patients

Abstract: Polyamine contents were assessed by mass spectrometry in 233 current foods and beverages. In order to reduce gut polyamine uptake, a polyamine reduced diet (PRD) and partial intermittent intestinal tract decontamination (PIITD) with neomycin or nifuroxazide was proposed as nutritional therapy to 33 prostate carcinoma patients, 30 of whom with hormone refractory prostate cancer (HRPC). Mean PRD observance was 22 +/- 19 (median: 16; range: 3-72) months. 10, 8 and 3 patients were respectively on PRD for more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 7 publications
4
75
0
2
Order By: Relevance
“…As previously shown by Bardocz et al, 43 some food ingredients contain large quantities of polyamines and preliminary clinical trials performed in metastatic hormone-refractory prostate cancer patients have revealed the feasibility of a nutrition therapy based upon a 6-month polyamine-reduced diet. 44,45 In conclusion, it is worth pointing out that the production process is very cheap and, by not involving organic solvents surfactants or particular capping strategies, it can be considered a "green chemistry" product. Nevertheless, the favorable magnetic properties of the material are guaranteed by optimizing the magnetic material/organic shell ratio.…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown by Bardocz et al, 43 some food ingredients contain large quantities of polyamines and preliminary clinical trials performed in metastatic hormone-refractory prostate cancer patients have revealed the feasibility of a nutrition therapy based upon a 6-month polyamine-reduced diet. 44,45 In conclusion, it is worth pointing out that the production process is very cheap and, by not involving organic solvents surfactants or particular capping strategies, it can be considered a "green chemistry" product. Nevertheless, the favorable magnetic properties of the material are guaranteed by optimizing the magnetic material/organic shell ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The foods that have a close relationship with an increased incidence of aging-associated diseases include Western desserts made from butter, cream, milk, egg, sugar, and animal fats that contain little polyamines (B. G. Cipolla et al, 2007;Nishibori et al, 2006;Nishimura et al, 2006;Soda, 2012).…”
Section: Epidemiologic Surveys and Dietary Polyaminesmentioning
confidence: 99%
“…A polyamine blocker therapy applied to explore the role of tumor-associated polyamines as immunosuppressive metabolites in oncogenesis and tumor progression and resulted that the applied therapy did not only block tumor growth but also promoted anticancer immune responses [79]. In prostate cancer patients it was shown that the reduction of dietary polyamine intake and partial intestinal decontamination was beneficial for patient quality of life and pain control [80].…”
Section: Reduced Polyamine Diet In Favor Of Cancer Patientsmentioning
confidence: 99%
“…Moreover, dietary putrescine reduced the ability of sulindac to suppress intestinal tumorigenesis in the mouse model suggesting that reducing polyamine metabolism and dietary polyamine levels might enhance strategies for colon cancer chemoprevention [42]. Consuming low polyamine diet and reducing bacterial gut production improved performance status and pain control in hormone refractory prostate cancer patients [80,89]. The association between high dietary polyamine intake and risk of colorectal adenoma was provided in literature [90,91].…”
Section: Reduced Polyamine Diet In Favor Of Cancer Patientsmentioning
confidence: 99%